2003
DOI: 10.1093/annonc/mdg334
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors after initiation of treatment in Waldenstrom’s macroglobulinemia

Abstract: Our findings suggest that advanced age and anemia appear to be the two dominant prognostic factors for survival after initiation of treatment in patients with WM. These two readily available parameters can stratify the patients into three distinct subgroups and may help the selection of appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Other adverse characteristics found in 3 or more studies were leucopenia, 6,7,20 high concentration of serum IgM paraprotein, 7,9,22 the pattern or the percentage of bone marrow infiltration, 18,19,23 a poor performance status, 18,20 and the presence of constitutional symptoms. 6,9,19,21 From these analyses, few prognostic indices have been proposed, but none of them has been widely accepted and used. Finally, in most series, both asymptomatic and symptomatic patients have been included.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other adverse characteristics found in 3 or more studies were leucopenia, 6,7,20 high concentration of serum IgM paraprotein, 7,9,22 the pattern or the percentage of bone marrow infiltration, 18,19,23 a poor performance status, 18,20 and the presence of constitutional symptoms. 6,9,19,21 From these analyses, few prognostic indices have been proposed, but none of them has been widely accepted and used. Finally, in most series, both asymptomatic and symptomatic patients have been included.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, agreement in the treatment algorithm of WM patients would be greatly facilitated by the availability of a simple and accurate prognostic index for overall survival similar to the International Prognostic Index for aggressive non-Hodgkin lymphoma, 15 the Follicular Lymphoma International Prognostic Index, 16 or the International Staging System for Multiple Myeloma. 17 In retrospective analyses, advanced age, [6][7][8][9][18][19][20][21][22] low hemoglobin concentration, [6][7][8][9][19][20][21][22] low platelet count, [6][7][8][18][19][20][21] low albumin concentration, 7,8,19,22 and elevated serum ␤2-microglobulin [7][8][9]19,20 were constantly associated with a poor clinical outcome. Other adverse characteristics found in 3 or more studies were leucopenia, 6,7,20 high concentration of serum IgM paraprotein, 7,9,22 the pattern or the percentage of bone marrow infiltration, 18,19,23 a poor performance status, 18,…”
Section: Introductionmentioning
confidence: 99%
“…Age had a poor prognostic significance in most studies. [19][20][21][22][23][24] Indeed, a large proportion of patients die from unrelated causes because of their advanced age at diagnosis. Several studies have shown a negative prognostic influence of high monoclonal IgM levels 22,25 but Dhodapkhar et al 5,26 found that patients with a low monoclonal concentration and a high beta 2 microglobulin had poor outcomes.…”
mentioning
confidence: 99%
“…WM remains an incurable disease with an overall medial survival of only 5-6 years and a median disease specific survival of 11.2 years 7 . Factors associated with poor prognosis include advanced age, high β2-microglobulin (β2M), cytopenias, low albumin, serum IgM monoclonal protein, and organomegaly [7][8][9][10][11] . Based on a series of 587 patients, an international prognostic scoring system (ISS-WM) was recently presented, table 1.…”
Section: Introductionmentioning
confidence: 99%